Investigating the potential of Beauveria bassiana as a biocontrol agent for Fullers rose weevil (Naupactus cervinus) - Shaw, P.W.; Wallis, D.R.; Nelson, T.L.; Jackson, T.A. (New Zealand Plant Protection, 2013)
Fullers rose weevil (FRW Naupactus cervinus) is a troublesome pest in pipfruit orchards since adult weevils often lay their eggs in irrigation sprinkler heads causing blockages throughout the season Adult weevils feed mainly on apple foliage and can damage and lay eggs on fruit The entomopathogenic fungus Beauveria bassiana was assessed as a biocontrol agent against Fullers rose weevil in a field trial at a Nelson pipfruit orchard with a large FRW population Larvae of the pest live in the soil and are susceptible to strains of the fungus The trial consisted of five randomised treated and untreated threetree apple plots (10 m2) A granular formulation of the fungus was applied by hand (50 g/m2) in May 2012 and irrigated into the soil Soil samples were collected in September 2012 and analysis showed the fungus had established in treated plots In treated plots average numbers of larvae were reduced by 70 and in four of the five plots emerging adults were reduced by an average of 80 These preliminary results indicate the potential for a granular formulation of Beauveria bassiana to be used as a broadcast application against FRW in orchards